2009
DOI: 10.1071/ea08203
|View full text |Cite
|
Sign up to set email alerts
|

Stress-strain properties of individual Merino wool fibres are minor contributors to variations in staple strength induced by genetic selection and nutritional manipulation

Abstract: This paper investigates the contribution of single fibre stress-strain properties to variations in staple strength induced by both selective breeding for staple strength and nutritional manipulation. Merino weaners (n = 40), selected from ‘sound’ and ‘tender’ lines of staple strength selection flocks, were allocated to feeding regimes designed to induce liveweight changes simulating typical Mediterranean seasonal changes. Average staple strength differed by 5 N/ktex between ‘sound’ and ‘tender’ selection flock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This increment in staple strength might be attributed to the treatments (G2 and G3) and related with increase in fiber diameter. These findings agree with previous studies by Thompson (1998) and Thompson and Hynd (2009) who found that an increase of 1 µm in minimum fiber diameter was associated with an increase in staple strength of about 5 N/ktex.…”
Section: Itemssupporting
confidence: 93%
“…This increment in staple strength might be attributed to the treatments (G2 and G3) and related with increase in fiber diameter. These findings agree with previous studies by Thompson (1998) and Thompson and Hynd (2009) who found that an increase of 1 µm in minimum fiber diameter was associated with an increase in staple strength of about 5 N/ktex.…”
Section: Itemssupporting
confidence: 93%
“…Due to its mechanical qualities, fully oriented gelatin fibers ( λ = 4) as produced in the present work are an eligible alternative to other protein fibers, such as sheep wool: single fibers of commercial sheep wool (measured with the same set‐up and test parameters) had an elastic modulus of 2.7 GPa and a tensile strength of 116 MPa. According to the literature, merino wool has higher stiffness (3.9 GPa) and tensile strength (212 MPa) . In Figure , the mechanical properties of the produced gelatin fibers are compared with major commodity fibers; the relevant properties were measured in‐house or taken from literature .…”
Section: Resultsmentioning
confidence: 99%
“…Because we were unable to undertake OFDA4000 measurements, it can only be speculated that the along fiber diameter profiles of the 24 and 43 N/ktex differed. Lamb [11] has observed that staple strength is influenced by factors other than individual fiber strength, and so may not relate as well to breakage in processing. As well as along fiber diameter profile variation, Lamb has observed that staple strength is also influenced by the extent to which fibers share the load in the ATLAS staple strength measurement, with one of the influences being variation in within staple fiber length.…”
Section: Resultsmentioning
confidence: 99%
“…In an extensive review of staple strength literature, Lamb [11] noted that staple strength is found to have almost no relationship to the average strength of bundles of fibers in the resulting tops or with subsequent yarn strength and spinning performance, apart from its effect via the length of the top. Lamb commented that "any variation in thickness along the fibre reduces the total load that can be supported and variation of fibres in thickness and length means that they can extend at different times and rates and so not share the load equally or not break at the same time, which reduces the peak force.…”
mentioning
confidence: 99%